2013
DOI: 10.1021/ja405239v
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of Curcumin Analogues for in Vivo Fluorescence Imaging and Inhibiting Copper-Induced Cross-Linking of Amyloid Beta Species in Alzheimer’s Disease

Abstract: In this article, we first designed and synthesized curcumin-based near infrared (NIR) fluorescence imaging probes for detecting both soluble and insoluble amyloid beta (Aβ) species, and then an inhibitor that could attenuate crosslinking of Aβ induced by copper. According to our previous results and the possible structural stereo-hindrance compatibility of the Aβ peptide and the hydrophobic/hydrophilic property of the Aβ13–20 (HHQKLVFF) fragment, NIR imaging probe CRANAD-58 was designed and synthesized. As exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
280
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 306 publications
(282 citation statements)
references
References 105 publications
(196 reference statements)
2
280
0
Order By: Relevance
“…CRANAD-2 could be considered a "smart" probe because it displayed a significant increase in fluorescence intensity, an emission blue shift, a lifetime change, and quantum yield improvement upon interacting with insoluble Aβ aggregates (47). However, we found that CRANAD-2 was not able to detect soluble Aβ species (46).…”
Section: Resultsmentioning
confidence: 66%
See 3 more Smart Citations
“…CRANAD-2 could be considered a "smart" probe because it displayed a significant increase in fluorescence intensity, an emission blue shift, a lifetime change, and quantum yield improvement upon interacting with insoluble Aβ aggregates (47). However, we found that CRANAD-2 was not able to detect soluble Aβ species (46).…”
Section: Resultsmentioning
confidence: 66%
“…In our previous studies, we designed the imidazole-containing curcumin analog CRANAD-17, which could compete specifically with the H13, H14 of Aβ peptides and lead to a reduction of copper-induced Aβ cross-linking in vitro (46). We performed a preliminary in vivo therapeutic treatment of 4-mo-old APP/PS1 mice with CRANAD-17 for 6 mo.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The binding sites and different binding models between the chiral metal complexes and Aβ1-40 were further confirmed by NMR spectroscopy [49][50][51][52][53] . The 1 H NMR signals of the aromatic moieties (F19F20) 49,50 of Aβ1-40 underwent remarkably change upon addition of complex 2, revealing their interactions associated with these units (Figure 4A and 4D).…”
Section: Esi-msmentioning
confidence: 99%